Pre-service Science Teachers’ Experiences in their Virtual Internship - Turingan, Archie; Joyce Silva, Erika; Formoso, Cinderella; Tindowen, Darin Jan C.; Batulan, Anjanette (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
The emergence of the Novel Corona Virus in 2019 has been the root cause of severe disruptions in economic opportunities and educational curriculum implementation, affecting people's daily lives worldwide. The pandemic has brought about changes in the educational system. The mode of learning and teaching has shifted from face-to-face to online education. This study aimed to explore the experiences of the pre-service science teachers as well as their recommendations to improve the implementation of online teaching delivery in their virtual internship. This basic qualitative research was carried out to explore the experiences of the pre-service science teachers as well as their recommendations to improve the implementation of online teaching delivery in their virtual internship. Twenty pre-service teachers took part in this study through an online interview. The findings revealed three major recurring themes: (1) Pre-deployment experiences of pre-service science teachers in their virtual internship; (2) Deployment experiences of pre-service science teachers in their virtual internship; and (3) Post-deployment experiences of pre-service science teachers in their virtual internship. The study concludes that pre-service science teachers have both positive and negative experiences during their virtual teaching internship. The recommendations of the informants focused primarily on the implementation of virtual internship program during the pandemic.